Wayang Kulit, Bulan Suro, dan Gereja Jawa: Memaknai Budaya sebagai Ruang Pendidikan Agama Kristen - Deo D. A. Pangestu; Yosep H. E. Baruno; Meksi Nesimnasi (Damai : Jurnal Pendidikan Agama Kristen dan Filsafat, 2026)
Wayang kulit and the Suro month tradition are important expressions of Javanese culture that have not been widely examined as integrated resources for contextual Christian Religious Education (PAK) within the Javanese Christian Church (GKJ). This study investigates the theological and educational values contained in both cultural traditions, evaluates the relevance of Bevans' synthesis model and Groome's Shared Christian Praxis approach for contextual PAK, and formulates practical principles for an inculturation-based educational framework rooted in Javanese culture. The research applies a library research method using a cultural hermeneutics approach. Primary sources consist of theological works by Bevans and Groome together with scholarly literature on wayang kulit and the Suro tradition, while secondary sources include Sinta- and Scopus-indexed journal articles published between 2015 and 2025. Data were analyzed through content analysis and theological interpretation. The findings indicate that the values of dharma, welas asih, and resistance to evil represented in wayang kulit correspond closely with Christian teachings, whereas the Suro practices of tirakat and laku prihatin align with Christian concepts of repentance and spiritual renewal. Bevans' and Groome's frameworks effectively support this inculturation process when accompanied by sound theological discernment to prevent syncretism. The study proposes three guiding principles—resonance, transformation, and continuity—as practical foundations for implementing culturally rooted PAK in GKJ.